Response-adapted lenalidomide maintenance in newly diagnosed myeloma: results from the phase III GMMG-MM5 trial - Goldschmidt, Hartmut; Mai, Elias K.; Dürig, Jan; Scheid, Christoph; Weisel, Katja C.; Kunz, Christina; Bertsch, Uta; Hielscher, Thomas; Merz, Maximilian; Munder, Markus; Lindemann, Hans-Walter; Hügle-Dörr, Barbara; et al. (Leukemia, 2020)
The MM5 trial aimed at demonstrating a progression-free survival (PFS) difference in continued vs. response-adapted (in case of complete response, CR) lenalidomide (LEN) maintenance therapy (MT) in newly diagnosed, transplant-eligible multiple myeloma (MM). Patients were equally randomized to receive induction therapy with PAd (bortezomib/doxorubicin/dexamethasone) or VCD (bortezomib/cyclophosphamide/dexamethasone), high-dose melphalan and autologous blood stem cell transplantation, and LEN consolidation, followed by either LEN MT for a fixed duration of 2 years (LEN-2Y) or until achievement of CR (LEN-CR, intention-to-treat population n = 502): arms A1:PAd + LEN-2Y (n = 125), B1:PAd + LEN-CR (n = 126), A2:VCD + LEN-2Y (n = 126), B2:VCD + LEN-CR (n = 125). In the LEN-CR group (B1 + B2), n = 88/17.5% patients did not start or discontinued LEN MT due to CR. There was no PFS (p = 0.60, primary endpoint) nor overall survival (OS) (p = 0.15) difference between the four study arms. On pooled LEN MT strategies, OS (hazard ratio, hazard ratio [HR] = 1.42, p = 0.03) but not PFS (HR = 1.15, p = 0.20) was shorter in LEN-CR (B1 + B2) vs. LEN-2Y (A1 + A2) groups. PFS was shortened on landmark analyses from the start of LEN MT in patients being in CR in the LEN-CR group (LEN-CR vs. LEN-2Y, HR = 1.84, p = 0.02). OS from first progression was shortened in the LEN-CR vs. LEN-2Y group (HR = 1.60, p = 0.01). LEN MT should be applied beyond CR for at least 2 years.
Gesehen am 09.09.2021